Assessment of risk factors in dogs with presumptive advanced canine cognitive dysfunction - MacQuiddy, Brittany; Moreno, Julie A.; Kusick, Breonna; McGrath, Stephanie (Frontiers in Veterinary Science, 2022)
Objectives The aim of this study was to investigate the potential risk factors involved in the development of presumptive advanced canine cognitive dysfunction (pACCD). Materials and Methods A questionnaire was developed to identify dogs with presumptive canine cognitive dysfunction (CCD) based on an adapted Canine Dementia Scale and to evaluate for potential risk factors among the presumptive advanced cognitive dysfunction group. The questionnaire was distributed to 7,574 owners of dogs (≥8 years of age) who presented to the CSU VTH between 2017 and 2020. Dogs were classified into four groups based on the Canine Dementia Scale score (normal, mild, moderate, and severe cognitive impairment) and two subgroups for the cognitively impaired groups based on the presence or absence of underlying medical conditions. Comparisons between normal and presumptive advanced cognitively impaired groups, with and without underlying medical conditions, were made against various risk factors. Chi-square tests and logistic regression analysis were used to determine associations between categorical variables and a p-value of less than 0.05 was considered indicative of evidence of association. Results The completed response rate for the questionnaire was 14.2% (1079/7574). Among those, 231 dogs were classified as having presumptive advanced cognitive dysfunction. The prevalence of presumptive advanced cognitive dysfunction in the included age groups was 8.1% in ages 8 to <11 years, 18.8% in ages 11 to <13 years, 45.3% in ages 13 to <15 years, 67.3% in ages 15 to <17 years, and 80% in ages >17 years. Dogs with a thin body condition score had the largest contribution to the chi-square statistic. Based on the logistic regression model, both age (p<0.001) and BCS (p=0.0057) are associated with presumptive ACCD. Conclusion and Relevance The chi-square test and logistic regression analysis both suggested an association between a thin body condition and an increased chance of cognitive decline. However, it is difficult to determine if the thin BCS in this group could be secondary to another confounding factor. The prevalence of cognitive dysfunction rapidly increased with age in this study. These findings warrant continued studies including veterinary evaluations to explore risk factors of canine dementia.